2019
DOI: 10.3390/cells8070684
|View full text |Cite
|
Sign up to set email alerts
|

HIPK2 Phosphorylates the Microtubule-Severing Enzyme Spastin at S268 for Abscission

Abstract: Abscission is the final step of cell division, mediating the physical separation of the two daughter cells. A key player in this process is the microtubule-severing enzyme spastin that localizes at the midbody where its activity is crucial to cut microtubules and culminate the cytokinesis. Recently, we demonstrated that HIPK2, a multifunctional kinase involved in several cellular pathways, contributes to abscission and prevents tetraploidization. Here, we show that HIPK2 binds and phosphorylates spastin at ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…To evaluate the effect of HIPK2 depletion over more than one cell cycle, cells were transfected with stealth siRNAs that have increased stability in cell culture than standard siRNAs. We showed that HIPK2 depletion delays abscission and induces accumulation of aberrant elongated midbodies and cytokinesis failure (Rinaldo et al, 2012;Pisciottani et al, 2019). During these studies, we also observed the appearance of a large fraction of cells with MBRs in the siHIPK2 cells compared to their relative siCtr ( Figures 1A,B, and Supplementary Figure S1).…”
Section: Hipk2 Depletion Leads To Mbr Accumulationmentioning
confidence: 55%
See 3 more Smart Citations
“…To evaluate the effect of HIPK2 depletion over more than one cell cycle, cells were transfected with stealth siRNAs that have increased stability in cell culture than standard siRNAs. We showed that HIPK2 depletion delays abscission and induces accumulation of aberrant elongated midbodies and cytokinesis failure (Rinaldo et al, 2012;Pisciottani et al, 2019). During these studies, we also observed the appearance of a large fraction of cells with MBRs in the siHIPK2 cells compared to their relative siCtr ( Figures 1A,B, and Supplementary Figure S1).…”
Section: Hipk2 Depletion Leads To Mbr Accumulationmentioning
confidence: 55%
“…In human cells, HIPK2 RNA interference (RNAi) and Spastin RNAi were obtained by using stealth siRNAs as in Pisciottani et al, 2019. Specific prevalidated stealth siRNAs by Life Technologies were used to obtain HIPK2 RNAi in mouse cells and CEP55 RNAi in human cells.…”
Section: Rna Interference and Expression Vector Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Control of HIP kinases involves dynamic changes in their intracellular localization, and also regulation of their protein abundance by multiple levels including regulated synthesis and decay ( D’Orazi et al, 2012 ; Ohnheiser et al, 2015 ; Wong et al, 2020 ). The best studied member of the HIPK family is HIPK2, a kinase that is involved in many different biological processes including the maintenance of basal cardiac functions, cell abscission, type I interferon-mediated antiviral immunity and neuronal survival ( Shang et al, 2018 ; Guo et al, 2019 ; Pisciottani et al, 2019 ). In addition, HIPK2 contributes to developmental and differentiation processes to control adipogenesis ( Sjölund et al, 2014 ), the development of various neuronal subtypes, angiogenesis, vasculogenesis, and hematopoiesis in different contexts ( Blaquiere and Verheyen, 2017 ).…”
Section: Introductionmentioning
confidence: 99%